A comprehensive proteomic and phosphoproteomic analysis of yeast deletion mutants of 14‐3‐3 orthologs and associated effects of rapamycin. Issue 2 (17th December 2014) - Paulo, Joao A.; Gygi, Steven P.; Pandey, Akhilesh; Moran, Michael F.
<x xml:space="preserve">Abstract</x> We applied a multiplexed, MS‐based strategy to interrogate the proteome and phosphoproteome of three yeast strains under two growth conditions in triplicate. The yeast proteins brain modulosignalin homologue (Bmh)1 and Bmh2, analogs to the 14‐3‐3 protein family, have a wide array of cellular functions including the regulation of phosphorylation events. Moreover, rapamycin is a drug that can regulate phosphorylation events. By performing a series of tandem mass tag 10‐plex experiments, we investigated the alterations in the proteome and phosphoproteome of wildtype and two deletion strains (bmh1Δ and bmh2Δ) of Saccharomyces cerevisiae treated with rapamycin and DMSO as a control. Our 3 × 3 + 1 strategy allowed for triplicate analysis of each of the three strains, plus an additional sample consisting of an equal mix of all samples. We quantified over 4000 proteins and 20 000 phosphorylation events. Of these, we quantified over 3700 proteins across all 20 samples and over 14 300 phosphorylation events within each drug treatment. In total, data collected from four tandem mass tag 10‐plex experiments required approximately 1 week of data collection on the mass spectrometer. This study underscores the complex cellular roles of Bmh1 and Bmh2 coupled with response to rapamycin treatment and emphasizes the utility of multiplexed proteomic techniques to elucidate comprehensive proteomes and phosphoproteomes.